Theoretical Study of Flourishing: The Role of Perceived Stress, Social Support, and Coping Strategy - Handy Satria Yudha; Siti Urbayatun (Universitas Ahmad Dahlan, 2020)
AbstractFlourishing is a combination of feeling good and functioning effectively. Flourishing includes not only cognitive, and affective aspects, but also behavior directed at productive actions. Then, it is known that the flourishing condition in a person is influenced by several factors namely; perceived stress, social support, and coping strategies. This study aims to discuss research findings related to the role of perceived stress, social support, and coping strategies on flourishing. Several research articles were obtained through an online search system of electronic research articles, namely PubMed, Google Scholar, and Science Direct. The keywords used in the search are perceived stress, stress, social support, coping style, coping strategy, and flourishing. A total of 13 articles were reviewed through filtering based on inclusion and exclusion criteria. The findings show that perceived stress, social support, and coping strategies have an important role in shaping flourishing conditions. Furthermore, the various instruments used in various articles vary greatly according to the researchers' concepts and approaches in looking at each variable.Keywords: perceived stress, social support, coping strategies, and flourishing